The Effect of Physical Activity on the Prevention of Degenerative Diseases of the Cardiovascular System - Liliana Puspa Sari; Heru Santosa; Garry Kuan (Window of Health : Jurnal Kesehatan, 2024)
Atherosclerotic plaque, which forms in blood arteries due to a lack of blood flow to the cells that produce blood flow, is a disease that causes a continuous decline in the function of body cells that characterizes degenerative diseases of the cardiovascular system. Through physical exercise, this study seeks to prevent several degenerative diseases of the cardiovascular system by reducing indicators of metabolic symptoms. The type of research applied is Action Research with the Spiral Model of Kemmis and Taggart, which is realized through the stages of Plan, Action, Observation, and Reflection. The sample used in this study has purposive sampling criteria, namely participant techniques based on age, namely 15-25 years old, who is studying at Bina Guna College of Sports and Health, and who has healthy body conditions and has symptoms of degenerative diseases of the cardiovascular system. The number of participants obtained was 30 people. 75% of participant data came from obesity measurements, 50% from hypertension, 45% from above-normal cholesterol levels, 20% from above-normal sugar measurements, and 50% from uric acid. The following metrics were used to assess the success of the physical activity model: (1) Body Mass Index (BMI) measurements were used to determine obesity levels; (2) blood pressure devices were used to measure hypertension; and (3) Autocheck was used to measure uric acid, sugar, and cholesterol. The implementation of two cycles led to a 30% decrease in obese patients, a 13% decrease in hypertension, a 13% decrease in cholesterol, a 10% decrease in blood sugar levels, and a 10% decrease in uric acid. The concept of physical fitness in the form of a movement activity concept developed as physical activity in the form of gymnastics based on structured and systematic movements, physical activity in the form of a daily activity schedule, and physical education as a diet as an example of a diet in carrying out activities, the prevention model through physical activity influences reducing the symptoms of degenerative diseases in the cardiovascular system.